Establishing a Bioluminescent Screening Platform to Identify Stromal-Mediated Chemoresistance in Leukaemia - Panting, Rhiannon (Curtin University, 2024)
The tumour microenvironment has been shown to support cancer progression and regulate responsiveness to drug treatment. In leukaemia, chemoresistance is often facilitated by stromal cells of the bone marrow microenvironment. In this project, we established a co-culture drug screening pipeline and discovered that the stromal cells conferred anthracycline resistance to BCR-ABL1+ chronic myeloid leukaemia. We further investigated the mechanism of chemoresistance, paving the way to design the most effective therapeutic approach for these patients.